The Effects of β-Alanine Supplementation on Muscle pH and the Power-Duration Relationship during High-Intensity Exercise - Black, Matthew I.; Jones, Andrew M.; Morgan, Paul T.; Bailey, Stephen J.; Fulford, Jonathan; Vanhatalo, Anni (Frontiers in Physiology, 2018)
Purpose: To investigate the influence of β-alanine (BA) supplementation on muscle carnosine content, muscle pH and the power-duration relationship (i.e., critical power and W′). Methods: In a double-blind, randomised, placebo-controlled study, 20 recreationally-active males (22 ± 3 y, V̇O2peak 3.73 ± 0.44 L∙min-1) ingested either BA (6.4 g/d for 28 d) or placebo (PL) (6.4 g/d) for 28 d. Subjects completed an incremental test and two 3-min all-out tests separated by 1 min on a cycle ergometer pre- and post-supplementation. Muscle pH was assessed using 31P-magnetic resonance spectroscopy (MRS) during incremental (INC KEE) and intermittent knee-extension exercise (INT KEE).Muscle carnosine content was determined using 1H-MRS. Results: There were no differences in the change in muscle carnosine content from pre- to post-intervention (PL: 1±16% vs. BA: -4±25%) or in muscle pH during INC KEE or INT KEE (P>0.05) between PL and BA, but blood pH (PL: 0.06±0.10 vs. BA: 0.09±0.13) during the incremental test was elevated post-supplementation in the BA group only (P<0.05). The changes from pre- to post supplementation in critical power (PL: -8±18 W vs. BA: -6±17 W) and W′ (PL: 1.8±3.3 kJ vs. BA: 1.5±1.7 kJ) were not different between groups. No relationships were detected between muscle carnosine content and indices of exercise performance. Conclusions: BA supplementation had no significant effect on muscle carnosine content and no influence on intramuscular pH during incremental or high-intensity intermittent knee-extension exercise. The small increase in blood pH following BA supplementation was not sufficient to significantly alter the power-duration relationship or exercise performance.